2014
DOI: 10.7550/rmb.43234
|View full text |Cite
|
Sign up to set email alerts
|

First record of the invasive greenhouse frog (Eleutherodactylus planirostris) in the Mexican Caribbean

Abstract: Biological invasions are widely recognized as a significant component of human-caused global environmental change, often resulting in the loss of biological diversity and ecosystem function (Hulme, 2003). The greenhouse frog Eleutherodactylus planirostris has direct development (no aquatic stage) and deposits its eggs in moist soil, which facilitate human-mediated colonization (Christy et al., 2007) through transportation in potted plants (e.g. Kraus et al., 1999;Kraus and Campbell, 2002).The greenhouse frog i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
5
0
4
Order By: Relevance
“…Further, prevailing surface currents in the eastern Caribbean Sea travel in a northwestern direction, which makes transport of flotsam from the Puerto Rican Bank to Saint Croix exceedingly difficult (Heatwole and MacKenzie, 1967). Whereas several studies have documented human-mediated transport of Eleutherodactylus frogs among Caribbean islands (Platenberg, 2007; Powell et al, 2011), and to mainland countries (Crawford et al, 2011; Heinicke et al, 2011; Cedeño-Vázquez et al, 2014) in the past 100–200 years, none has reported evidence of colonization of islands by these anurans via rafting over the same time period. For instance, E. coqui (Common Coquí), a co-distributed relative of E. antillensis , was introduced to Saint Croix, Saint John, and Saint Thomas (Schwartz and Thomas, 1975; Schwartz and Henderson, 1991), most likely as a result of horticultural and landscaping imports from Puerto Rico (Platenberg, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Further, prevailing surface currents in the eastern Caribbean Sea travel in a northwestern direction, which makes transport of flotsam from the Puerto Rican Bank to Saint Croix exceedingly difficult (Heatwole and MacKenzie, 1967). Whereas several studies have documented human-mediated transport of Eleutherodactylus frogs among Caribbean islands (Platenberg, 2007; Powell et al, 2011), and to mainland countries (Crawford et al, 2011; Heinicke et al, 2011; Cedeño-Vázquez et al, 2014) in the past 100–200 years, none has reported evidence of colonization of islands by these anurans via rafting over the same time period. For instance, E. coqui (Common Coquí), a co-distributed relative of E. antillensis , was introduced to Saint Croix, Saint John, and Saint Thomas (Schwartz and Thomas, 1975; Schwartz and Henderson, 1991), most likely as a result of horticultural and landscaping imports from Puerto Rico (Platenberg, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a generalist species that occurs naturally in Cuba, the Cayman Islands, and the Bahama Islands. In addition, introduced populations are known from Jamaica, Grenada (although apparently extirpated; Henderson and Powell 2018), the Caicos Islands, the southeastern United States, Mexico, Honduras, the Miskito Cays of Nicaragua, Panama, and the Pacific islands of Hawaii and Guam (for reviews see Powell 2009 andCedeño-Vázquez et al 2014). West Indian eleutherodactylid frogs are frequent prey of a variety of predators (see Henderson and Powell 2009 for a review).…”
Section: A B Cmentioning
confidence: 99%
“…Cabe mencionar que se registró una mayor abundancia de E. planirostris en los sitios cercanos al área donde la especie fue reportada por primera vez en 2010 (Cedeño-Vázquez et al, 2014), por lo cual no se descarta la posibilidad de que en la misma se localice el punto de su introducción en el Caribe mexicano. Playa del Carmen es una ciudad predominantemente turística, lo que demanda la introducción de plantas exóticas para decorar las instalaciones hoteleras, factor que contribuye a la translocación de esta rana fuera de su área de distribución nativa, como consecuencia de la exportación de plantas tropicales ornamentales que le sirven como medio de transporte desde su área de origen (Kraus y Campbell, 2002;Pough, Stewart y Thomas, 1977;Villa, 2015).…”
Section: Teoría Y Praxis Núm 21unclassified